ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA KONSUMEN INDUSTRY/ TOKO BAKERY DI KOTA BENGKULU) - Novrianda, Herry (Institut Agama Islam Bengkulu, 2016)
The objective of this research is to analyze the effect of product quality, service quality and price toward customer satisfaction on industry/ bakery shop in the Bengkulu city. This study is a descriptive research which aims to clarify the relationship or influence that exist between the variables studied. The type of data used a primary data that is collected from questionnaires. Respondents of this study is the customer industry/ bakery shop in Bengkulu city as many 240 people were taken with the judgemental (purposive sampling) technique. The methods of data analysis used are descriptive analysis by using the mean, frequency distribution table and multiple linear regression analysis. Based on the analysis, the result that the simultaneously product quality, service quality, and price is significantly impact on customer satisfaction industry/ bakery shop in the Bengkulu city. The next in partial product quality and service quality is positively and significantly impact on customer satisfaction industry/ bakery shop in the Bengkulu city, while the price is negative and significantly impact on customer satisfaction industry/ bakery shop in the Bengkulu city.Keywords: Customer Satisfaction, Product Quality, Service Quality, Price